Dose-Effect Determination of a Neuroprotector Fraction Standardized in Coumarins of Tagetes lucida and Bioavailability - Anislada Santibáñez; Maribel Herrera-Ruiz; Manasés González-Cortazar; Pilar Nicasio-Torres; Ashutosh Sharma; Enrique Jiménez-Ferrer (MDPI AG, 2023)
Neurodegeneration has been associated with chronic inflammation states in the brain. For this reason, attention has been directed to drugs indicated as anti-inflammatory as possible therapies for the treatment of said conditions. Tagetes lucida has been widely used as a folk remedy in illnesses associated with the central nervous system and inflammatory ailments. Among the compounds that stand out in the plant against these conditions are coumarins, such as 7-O-prenyl scopoletin, scoparone, dimethylfraxetin, herniarin, and 7-O-prenylumbelliferone. Therefore, the relationship between the therapeutic effect and the concentration was evaluated through pharmacokinetic and pharmacodynamic studies, including vascular permeability evaluation by blue Evans and pro- and anti-inflammatory cytokines quantification, under a neuroinflammation model induced by lipopolysaccharide by the oral administration of three different doses (5, 10, and 20 mg/kg) of a bioactive fraction of T. lucida. In the present study, it was found that all doses showed a neuroprotective and immunomodulatory effect, although the doses of 10 and 20 mg/kg were able to exert their effect for a longer time and to a greater extent. The protective effects of the fraction may be mainly associated with the DR, HR, and SC coumarins due to their structural profile and plasmatic and brain tissue bioavailability.